2019
DOI: 10.1042/bsr20181539
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and persistent antidepressant-like effects of Chaihu-jia-Longgu-Muli-tang are associated with instantly up-regulated BDNF in the hippocampus of mice

Abstract: Conventional antidepressants have a disadvantage in delayed onset of efficacy. Here, we aimed to evaluate the immediate and persistent antidepressant-like action of a classic herbal medicine Chaihu-jia-Longgu-Muli decoction (CLM) as well as the action of CLM on hippocampal brain-derived neurotrophic factor (BDNF) over time. CLM consists of Xiaochaihu decoction (XchD), Longgu-Muli (LM) and several other herbs. The contribution of constituent herbal formula XchD and other parts of CLM was also assessed. Followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…CLMD is one of the most common prescriptions used in the treatment of mental diseases in TCM. Clinical studies have found that CLMD has the effect of psychotropic drugs and have shown a significant antidepressant effect on animal models [37,38]. It can regulate the hypothalamopituitary-adrenal system dysfunction by preventing the dopaminergic and serotonergic transmission in the prefrontal cortex [39] and upregulate the expression of the brain-derived neurotrophic factor (BDNF) to alleviate the depression-like state induced by chronic stress [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLMD is one of the most common prescriptions used in the treatment of mental diseases in TCM. Clinical studies have found that CLMD has the effect of psychotropic drugs and have shown a significant antidepressant effect on animal models [37,38]. It can regulate the hypothalamopituitary-adrenal system dysfunction by preventing the dopaminergic and serotonergic transmission in the prefrontal cortex [39] and upregulate the expression of the brain-derived neurotrophic factor (BDNF) to alleviate the depression-like state induced by chronic stress [37].…”
Section: Discussionmentioning
confidence: 99%
“…It can regulate the hypothalamopituitary-adrenal system dysfunction by preventing the dopaminergic and serotonergic transmission in the prefrontal cortex [39] and upregulate the expression of the brain-derived neurotrophic factor (BDNF) to alleviate the depression-like state induced by chronic stress [37]. It also has immediate and long-lasting antidepressant effects by enhancing BDNF expression in the hippocampus [38]. Chaihu (Radix Bupleuri) and Huang Qin (Radix Scutellariae) are the key drugs in many prescriptions for mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…), and Da Zao ( Ziziphus jujuba Mill.). The researchers found that CLM produced immediate and lasting antidepressant activity by enhancing hippocampal BDNF expression, in which components of the Xiaochuhu decoction played a major role [ 94 ]. In addition, CLM induced rapid antidepressive-like effects in OB mice, which may be due to the reversal of abnormal expression of AMPA and NMDA receptors in the PFC and the related Akt-mTOR signaling [ 95 ].…”
Section: Representative Prescriptionmentioning
confidence: 99%
“…Moreover, given its efficacy, it is also commonly used for the treatment of depression. Previous studies have established that the efficacy of the Chaihu Longgu Oyster Decoction is statistically significant (6)(7)(8)(9). Adjustments have been made to the Chaihu Longgu Oyster Decoction, with the removal of Qian Dan and replacing Ren Shen with Dang Shen, yielding a remarkable clinical effect.…”
Section: Introductionmentioning
confidence: 99%